2022
DOI: 10.21037/tau-22-125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregnancy and neonatal outcomes of intracytoplasmic sperm injection performed with frozen versus fresh testicular sperm

Abstract: Background: It remains controversial whether there is a difference in the prognosis of intracytoplasmic sperm injection (ICSI) using frozen or fresh testicular sperm in patients with obstructive azoospermia (OA). Moreover, in the available studies, few have tracked neonatal outcomes. This study aimed to compare the pregnancy and neonatal outcomes of ICSI using cryopreserved sperm versus fresh sperm collected by testicular sperm aspiration (TESA).Methods: A total of 317 OA patients treated with ICSI in a univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…These findings align with prior research by Wu et al [21], who reported no significant differences in preterm birth rate (P ¼ 0:224) and multiple pregnancy rate (P ¼ 0:329) between frozen and fresh testicular sperm groups. Furthermore, our study revealed a marginally higher clinical pregnancy rate (51.2% vs. 48.5%, P ¼ 0:673) and live birth rate (44.4% vs. 40.8%, P ¼ 0:564) in the frozen testicular sperm group, consistent with findings by Meng et al [22], who attributed these outcomes to the selection of with high motility during frozen-thawed process.…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with prior research by Wu et al [21], who reported no significant differences in preterm birth rate (P ¼ 0:224) and multiple pregnancy rate (P ¼ 0:329) between frozen and fresh testicular sperm groups. Furthermore, our study revealed a marginally higher clinical pregnancy rate (51.2% vs. 48.5%, P ¼ 0:673) and live birth rate (44.4% vs. 40.8%, P ¼ 0:564) in the frozen testicular sperm group, consistent with findings by Meng et al [22], who attributed these outcomes to the selection of with high motility during frozen-thawed process.…”
Section: Discussionsupporting
confidence: 92%
“…A large cohort involving 272 males with cancers reported a live birth rate of 62.1% per patient, comparable to the non-cancer infertile population ( 205 ). Specifically, the outcomes of couples using testicular sperm do not differ between fresh and frozen-thawed sperm among patients with Klinefelter syndrome ( 212 , 213 ), obstructive azoospermia ( 214 ), and non-obstructive azoospermia ( 215 , 216 ). But the cumulative live birth rate was lower than that of ejaculated sperm ( 216 , 217 ).…”
Section: Clinical Outcomes After Fertility Preservationmentioning
confidence: 99%